1986
DOI: 10.1111/j.1348-0421.1986.tb02993.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Specific Prevalence of Hepatitis B e Antigen (HBeAg) and Antibody to HBeAg (Anti‐HBe) among Asymptomatic Hepatitis B Surface Antigen (HBsAg) Carriers in Okinawa and Kyushu, Japan

Abstract: A total of 1,741 asymptomatic hepatitis B surface antigen (HBsAg)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We previously reported that there was a significant epidemiological difference in the clinical course of chronic HBV infection, even within one country such as Japan. Patients in Fukuoka had higher rates of HBeAg positivity and liver damage than those in Okinawa, and the former less frequently had HBeAg negativity than the latter 6,7 . This has been recognized as reflecting hepatitis B surface antigen (HBsAg) subtype, because HBsAg subtypes adr and adw are most common in Fukuoka and Okinawa, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that there was a significant epidemiological difference in the clinical course of chronic HBV infection, even within one country such as Japan. Patients in Fukuoka had higher rates of HBeAg positivity and liver damage than those in Okinawa, and the former less frequently had HBeAg negativity than the latter 6,7 . This has been recognized as reflecting hepatitis B surface antigen (HBsAg) subtype, because HBsAg subtypes adr and adw are most common in Fukuoka and Okinawa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Patients in Fukuoka had higher rates of HBeAg positivity and liver damage than those in Okinawa, and the former less frequently had HBeAg negativity than the latter. 6,7 This has been recognized as reflecting hepatitis B surface antigen (HBsAg) subtype, because HBsAg subtypes adr and adw are most common in Fukuoka and Okinawa, respectively. Also, the rates and ages of seroconversion from HBeAg to anti-HBe are higher and occur at a younger age in patients with HBsAg subtype adw than in those with adr.…”
Section: Introductionmentioning
confidence: 99%
“…The results relative to the general distribution of serological markers of HBV in the total sample considered, particularly the prevalence of HBV-DNA, HBeAg and anti-HBe in asymptomatic carriers in Ethiopia show differences when compared with those from countries of similarly high levels of endemicity, such as the Middle East (21) and southeastern Asia (13,15,23).…”
Section: Discussionmentioning
confidence: 99%
“…This is also confirmed by the presence of high rates of reinfection, as it may be deduced by the presence of individuals with simultaneous positivity for HBsAg and anti-HBs and, in some cases, also for HBV-DNA. It appears that the prevalence of HBeAg-positive individuals in Ethiopia is lower than that in Asia (15,16,23), whereas that of anti-HBe is higher in comparable types of population and age (10). A faster seroconversion may therefore be hypothesized in African populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation